Percentage of Circulating CD8+ T Lymphocytes is Associated with Albuminuria in Type 2 Diabetes Mellitus - Lei, L.; Mao, Y.; Meng, D.; Zhang, X.; Cui, L.; Huo, Y.; Wang, Y. (Experimental and Clinical Endocrinology & Diabetes, 2014)
T lymphocytes have been demonstrated to play a role in the development of diabetic proteinuria. However, the alteration of circulating T lymphocytes has not been investigated in a type 2 diabetic cohort. A cross-sectional study was conducted in Peking University Aerospace Center Hospital. 510 participants were type 2 diabetes mellitus, 30–70 years of age. Patients with immune disease, medical conditions that affect immune function, infection, or end-organ damage were excluded. The percentage of circulating CD8+ T lymphocytes was significantly associated with albuminuria in the cohort. The impact of albuminuria to CD8+ T lymphocytes in a multivariate linear regression model was indicated by the B- coefficient (95% confidence interval) 1.812 (0.204–3.421, P=0.03). Our data first showed that the percentage of circulating CD8+ T cells is associated with albuminuria in type 2 diabetes mellitus, which may support the rationality of systemic inhibition of T lymphocytes in treating albuminuria in these patients.
Keywords: T lymphocytes; type 2 diabetes mellitus; albuminuria; CD8